Effect of progesterone levels on the hCG trigger day and the progesterone-to-basal progesterone ratio on pregnancy outcomes in fresh IVF/ICSI cycles with GnRH antagonist protocol: a retrospective cohort study - Guan, Lu; Wu, Haicui; Li, Yuan; Liang, Qihui; Zhen, Xina; Xiang, Shan; Lian, Fang (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to analyze the effect of progesterone (P) levels on the human chorionic gonadotropin (hCG) trigger day and the progesterone on hCG day-to-basal progesterone (PhCG/Pbasal) ratio on pregnancy outcomes in patients with a normal ovarian response undergoing fresh embryo transfer in a gonadotropin-releasing hormone antagonist (GnRH-ant) cycle.Materials and methodsThis was a single-center retrospective study including 1,981 GnRH-ant protocol cycles with fresh embryo transfer from January 2017 to December 2023. All enrolled patients with a normal ovarian response were divided into four groups according to P levels on the hCG trigger day and PhCG/Pbasal ratio based on cutoffs determined by receiver operating characteristic (ROC) analysis: Group A (P level<1.06 ng/mL and PhCG/Pbasal ratio<1.2), Group B (P level <1.06 ng/mL and PhCG/Pbasal ratio≥1.2), Group C (P level≥1.06 ng/mL and PhCG/Pbasal ratio<1.2) and Group D (P level≥1.06 ng/mL and PhCG/Pbasal ratio≥1.2). Subsequently, the associations between clinical variables and pregnancy outcomes were analyzed and compared across the groups.ResultsThe positive pregnancy rate (53.5%), clinical pregnancy rate (50.0%), live birth rate (LBR) (43.6%) and singleton rate (36.7%) were significantly higher in Group A than in the other three groups (all P<0.001). Furthermore, the LBR (30.2% vs. 22.4%) and singleton rate (23.8% vs. 17.1%) were significantly higher in Group C than in Group D (both P<0.05). The early miscarriage rate in Group A was comparable to Group B, but lower than in Group C and D (10.6% vs. 14.6% vs. 17.4% vs. 20.4%, P = 0.016). After multivariable logistic regression analysis, the LBR was highest in Group A (Group B vs.A: AOR = 0.437, 95% CI = 0.316-0.603, P<0.001; Group C vs.A: AOR = 0.512, 95% CI = 0.391-0.670, P<0.001; Group D vs.A: AOR = 0.325, 95% CI = 0.240-0.441, P<0.001).ConclusionsFor patients with a normal ovarian response undergoing the GnRH-ant protocol, even a slight elevation in P levels on the hCG trigger day affected LBR. Moreover, the impact of the PhCG/Pbasal ratio on pregnancy outcomes also warrants attention. A serum P level < 1.06 ng/mL on the hCG trigger day and PhCG/Pbasal ratio < 1.2 were associated with a significantly higher LBR. When the PhCG/Pbasal ratio ≥ 1.2, the LBR declined regardless of P levels on hCG trigger day. These findings highlight the potential for incorporating PhCG/Pbasal ratio considerations into individualized clinical management strategies to optimize pregnancy outcomes.